The implementation of the national examination in Indonesian: Evaluating its usefulness and drawbacks - Ezis Japar Sidik (Universitas Sarjanawiyata Tamansiswa, 2020)
National Examination (NE) in education system always becomes a debatable issue particularly in Indonesia. One of the never-ending discussions is that the disadvantages of the NE is assumed to overweigh its advantages that leads the government to plan the withdrawal of the NE in the future. Before the withdrawal of the NE is undertaken, the government needs to further consider some aspects in regard to the usefulness and drawbacks of the NE from different aspects. Hence, this paper will address three aspects of the NE implementation in Indonesia namely its social impacts on students and other parties, lack of usefulness of the NE results and potential misleading and inaccurate information of the NE results. Expectedly, the decision, whether it is to withdraw or maintain the NE, can be beneficial for the improvement of the national education quality.